Greenhouse gas calculator at farm level addressed to the growers - Carmen M. Torres; Assumpció Antón; Francesc Ferrer; Francesc Castells (The International Journal of Life Cycle Assessment, 2017)

Pitfalls in the diagnosis of biallelic PMS2 mutations - Marina Antelo; Daniela Milito; Jennifer Rhees; Enrique Roca; Miguel Barugel; Miriam Cuatrecasas; Leticia Moreira; Maria Liz Leoz; Sabela Carballal; Teresa Ocaña; Maria Pellisé; Antoni Castells; et al. (Familial Cancer, 2015)

Human Health Risks Derived from Dietary Exposure to Toxic Metals in Catalonia, Spain: Temporal Trend - Gemma Perelló; Juan M. Llobet; Jesús Gómez-Catalán; Victòria Castell; Francesc Centrich; Martí Nadal; José L. Domingo (Biological Trace Element Research, 2014)

A comparison of the GHG emissions caused by manufacturing tissue paper from virgin pulp or recycled waste paper - Eskinder Demisse Gemechu; Isabela Butnar; Jordi Gomà-Camps; Alfred Pons; Francesc Castells (The International Journal of Life Cycle Assessment, 2013)

Life cycle assessment of fuel ethanol from sugarcane in Argentina - María José Amores; Fernando Daniel Mele; Laureano Jiménez; Francesc Castells (The International Journal of Life Cycle Assessment, 2013)

The Psychological Impact of a False-Positive Screening Mammogram in Barcelona - Rebecca Espasa; Cristiane Murta-Nascimento; Ramón Bayés; Maria Sala; Montserrat Casamitjana; Francesc Macià; Xavier Castells (Journal of Cancer Education, 2012)

Phenotypic characterization and risk factors for interval breast cancers in a population-based breast cancer screening program in Barcelona, Spain - Laia Domingo; Maria Sala; Sònia Servitja; Josep Maria Corominas; Francisco Ferrer; Juan Martínez; Francesc Macià; Maria Jesús Quintana; Joan Albanell; Xavier Castells (Cancer Causes & Control, 2010)

Alternatives for Reducing the Environmental Impact of the Main Residue From a Desalination Plant - Montse Meneses; Jorgelina C. Pasqualino; Raquel Céspedes‐Sánchez; Francesc Castells (Journal of Industrial Ecology, 2010)
Summary One of the most important problems today is the scarcity of fresh water safe enough for human, industrial, and agricultural use. Desalination is an alternative source of fresh water supply in areas with severe problems of water availability. Desalination plants generate a huge amount of brine as the main residual from the plant (about 55% of collected seawater). Because of that, it is important to determine the best environmental option for the brine disposal. This article makes a global environmental analysis, under Spanish conditions, of a desalination plant and an environmental assessment of different final brine disposals, representing a range of the most common alternatives: direct disposal, wastewater treatment plant (WWTP) outflow dilution, and dilution with seawater. The environmental profile of the plant operation and a comparison of the brine final disposal alternatives were established by means of the life cycle assessment (LCA) methodology. From an analysis of the whole plant we observed that the highest environmental impact was caused by energy consumption, especially at the reverse osmosis stage, while the most relevant waste was brine. From an analysis of brine final disposal we have elaborated a comparison of the advantages and detriments of the three alternatives. As all of them might be suitable in different specific situations, the results might be useful in decisions about final brine disposal.

Association of MUTYH and MSH6 germline mutations in colorectal cancer patients - María Dolores Giráldez; Francesc Balaguer; Trinidad Caldés; Ana Sanchez-de-Abajo; Nuria Gómez-Fernández; Clara Ruiz-Ponte; Jenifer Muñoz; Pilar Garre; Victoria Gonzalo; Leticia Moreira; Teresa Ocaña; Joan Clofent; et al. (Familial Cancer, 2009)

Integrated life-cycle and risk assessment for industrial processes - Guido Sonnemann; Francesc Castells; Marta Schuhmacher; Michael Hauschild (The International Journal of Life Cycle Assessment, 2004)

Electrical and electronic practical ecodesing guide - Julio Rodrigo; Francesc Castells (The International Journal of Life Cycle Assessment, 2003)

Geographical and technological differences in Life Cycle Inventories shown by the use of process models for waste incinerators - Andreas Ciroth; Marcel Hagelüken; Guido W. Sonnemann; Francesc Castells; Günter Fleischer (The International Journal of Life Cycle Assessment, 2002)

Geographical and technological differences in life cycle inventories shown by the use of process models for waste incinerators part I. technological and geographical differences - Andreas Ciroth; Marcel Hagelüken; Guido W. Sonnemann; Francesc Castells; Günter Fleischer (The International Journal of Life Cycle Assessment, 2002)